Mihailo Konstantinović on right of reply and on abuse of right of reply bonus: Author's understanding of right of reply - Vodinelić Vladimir V. (Anali Pravnog Fakulteta u Beogradu)
Mihailo Konstantinović authored the region's first monography on right of reply in 1926-1927. His monography promoted the French model of right to reply, as opposed to the German model adopted in local literature, the courts and legislation. He argued that French solution was stricter for the press, but less stringent for a rights holder. He defended the position of the relative nature of right, which could be controlled by implementation of the abuse of right doctrine. The author analyzes: the suitability of the terms réponse and others; rights close to right of reply; the purpose and nature of right of reply; exceptions to the right and prohibition of abuse of rights as subsidiary exception; the special place of right of reply among another subjective rights; right of reply not corresponding to legal binary code, representing a juncture of law and legal indifference; possessory protection vs. personality protection through reply.